FORMATION OF INFORMATION COMPETENCE TEACHERS AS A PEDAGOGICAL PROBLEM - Poberezhna, N.O. (Pedagogy of Higher and Secondary Education, 2009)
The article reveals the notion of competence as a complex individual state. The ways of information competence formation as a result of theoretical knowlodge intergration have been considered.